المدخل البنائي في تعليم اللغة العربية - Ana Achoita (Tadris : Jurnal Penelitian dan Pemikiran Pendidikan Islam, 2017)
Teaching materials are important element in learning besides one of learning source. This statement could be implemented when those materials prepared according to right procedures as well as their arrangement principles, namely: language, culture and education besides teaching methods. However, some teaching materials and exercises are not relevant to provided materials (curriculum) and not related to students lives. Therefore, the students are inactive towards delivered subjects. One of the approach used in foreign language teaching is constructivism approach, which means a learning approach emphasizing students active roles in building knowledge and their involvement in teaching and learning.